2020
DOI: 10.1002/hep.31276
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in Liver Disease and Beyond: Can the COVID‐19 Crisis Lead to Action?

Abstract: Evidence strongly supports that access to specialty gastroenterology or hepatology care in cirrhosis is associated with higher adherence to guideline-recommended care and improves clinical outcomes.Presently, only about one half of acute care hospitalizations for cirrhosis-related complications result in inpatient specialty care and the current hepatology workforce cannot meet the demand of patients with liver disease nationwide, particularly in less densely populated areas and in community-based practices not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
141
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(148 citation statements)
references
References 13 publications
1
141
0
1
Order By: Relevance
“…Of those seen for hepatic, biliary, and pancreatic disorders, 77.3% expressed willingness to use telehealth in the future, which did not meet the high satisfaction threshold of 80%. However, 86.4% of these patients indicated that their concerns were addressed by the provider, and this is consistent with the findings of a recent study by Serper et al 20 Patients seen for follow-up care, medication-related issues, and preprocedural appointments were particularly satisfied with their virtual visits. In these groups, telehealth is particularly effective because it is much more convenient for the patient and thus improves the overall care experience.…”
Section: Telehealth and The Triple Aimsupporting
confidence: 87%
“…Of those seen for hepatic, biliary, and pancreatic disorders, 77.3% expressed willingness to use telehealth in the future, which did not meet the high satisfaction threshold of 80%. However, 86.4% of these patients indicated that their concerns were addressed by the provider, and this is consistent with the findings of a recent study by Serper et al 20 Patients seen for follow-up care, medication-related issues, and preprocedural appointments were particularly satisfied with their virtual visits. In these groups, telehealth is particularly effective because it is much more convenient for the patient and thus improves the overall care experience.…”
Section: Telehealth and The Triple Aimsupporting
confidence: 87%
“…Furthermore, on March 6th, 2020, The Centers for Medicare & Medicaid Services (CMS) mentioned that it would temporarily pay physicians to provide telemedicine services for beneficiaries across US [9,14,[17][18][19][20]. CMS now allow medical-care providers to utilize devices such as smartphones and electronic devices to treat patients [15,16,[21][22][23]. Additionally, on March 17th, 2020 the U.S. Department of Health and Human Services Office for Civil Rights mentioned that during the COVID-19 health emergency, medical practitioners may telemedicine solutions [20], such as MyChart to support patient care [14,15,24].…”
Section: Legislations That Support Deployment Of Telemedicine During mentioning
confidence: 99%
“…Few studies have been published in liver diseases [7]. Telemedicine has been used in HCV treatment and in the evaluation of patients with cirrhosis and hepatocellular carcinoma [11][12][13][14]. Two recent studies showed that telehealth was highly effective in the management of post-transplant patients and in identifying candidates for liver transplantation [15,16].…”
Section: Discussionmentioning
confidence: 99%